2016
DOI: 10.1111/clr.12825
|View full text |Cite
|
Sign up to set email alerts
|

Healing at implants installed concurrently to maxillary sinus floor elevation with Bio‐Oss® or autologous bone grafts. A histo‐morphometric study in rabbits

Abstract: Both Bio-Oss granules and autologous bone grafts contributed to the healing at implants installed immediately in elevated sinus sites in rabbits. Bio-Oss maintained the dimensions, while autologous bone sites lost 2/3 of the volume between the two periods of observation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 19 publications
4
38
0
Order By: Relevance
“…While between 2 and 4 weeks of healing the reduction in percentages was >10%, the reduction between 2 and 8 weeks of healing reached 46%–49%. This outcome is in agreement with other experiments in rabbits (Caneva et al, ; De Santis, Lang, et al, ; Iida et al, ; Scala et al, ). The shrinkage observed in the present study was obviously due to the concomitant resorption of the xenograft used that was not replaced by a corresponding amount of newly formed bone.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…While between 2 and 4 weeks of healing the reduction in percentages was >10%, the reduction between 2 and 8 weeks of healing reached 46%–49%. This outcome is in agreement with other experiments in rabbits (Caneva et al, ; De Santis, Lang, et al, ; Iida et al, ; Scala et al, ). The shrinkage observed in the present study was obviously due to the concomitant resorption of the xenograft used that was not replaced by a corresponding amount of newly formed bone.…”
Section: Discussionsupporting
confidence: 93%
“…While between 2 and 4 weeks of healing the reduction in percentages was >10%, the reduction between 2 and 8 weeks of healing reached 46%-49%. This outcome is in agreement with other experiments in rabbits De Santis, Lang, et al, 2017;Iida et al, 2017;Scala et al, 2012 and experimental studies in monkeys (Cricchio et al, 2009;Cricchio, Palma, et al, 2011) to secure the repositioned bone plate onto the antrostomy in sinus floor elevation without bone fillers.…”
Section: New Mineralize Bone % Xenograftsupporting
confidence: 92%
“…As a general rule, bone regeneration is more effective in defects which are completely surrounded by vital bone, because neoangiogenesis and migration of mesenchymal osteoprogenitors cells are the most important factors in promoting osseous healing (Carano & Filvaroff, ; Retzepi & Donos, ). A close contact between grafting material and bone walls is also crucial for a fast and effective delivery in the regeneration area of nutrients, oxygen supply, and osteogenesis mediators (e.g., bone morphogenetic proteins, alkaline phosphatase, osteopontin, osteonectin, osteocalcin) at the early stages of healing (De Santis et al., ; Scala et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…It was certainly found that, in vitro the Schneiderian membrane possess osteogenic capability and participates in the formation of bone after MSFA. However, the regenerative/reparative potential of the Schneiderian membrane in vivo has not been extensively evidenced . On the other side, understanding the maxillary sinus as a contained defect, the adjacent walls are the major responsible for the nutrients and oxygen supply needed to achieve predictable regeneration at the early stages of healing …”
Section: Discussionmentioning
confidence: 99%